2020
DOI: 10.1002/jcp.30211
|View full text |Cite
|
Sign up to set email alerts
|

The impact of culture dimensionality on behavioral epigenetic memory contributing to pluripotent state of iPS cells

Abstract: Three‐dimensional (3D) culture platforms have been explored to establish physiologically relevant cell culture environment and permit expansion scalability; however, little is known about the mechanisms underlying the regulation of pluripotency of human induced pluripotent stem cells (hiPSCs). This study elucidated epigenetic modifications contributing to pluripotency of hiPSCs in response to 3D culture. Unlike two‐dimensional (2D) monolayer cultures, 3D cultured cells aggregated with each other to form ball‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…This confirms that the cells adapt to culture environment through the alteration of the Rho-Rho kinase-phospho-myosin pathway, influencing the epigenetic modifications and the transcription factors that contribute to their inherent states (Thanuthanakhun et al, 2021). Studies using ESCs and iPSC cultures revealed that the time-dependent regulation of two key bivalent epigenetic marks, histone H3 trimethylation at lysine 4 (H3K4me3) and histone H3 trimethylation at lysine 27 (H3K27me3), could contribute to the maintenance of the stem cell state and differentiation potential (Harikumar and Meshorer, 2015;Li et al, 2018;Thanuthanakhun et al, 2021). This regulation can take place through epigenetic changes and may be manifested as a "memorizer."…”
Section: Identifying Criteria and Indicators For Assessing External Forcing And Internal Variability-generated Uncertainly In Stem Cell Bsupporting
confidence: 60%
See 3 more Smart Citations
“…This confirms that the cells adapt to culture environment through the alteration of the Rho-Rho kinase-phospho-myosin pathway, influencing the epigenetic modifications and the transcription factors that contribute to their inherent states (Thanuthanakhun et al, 2021). Studies using ESCs and iPSC cultures revealed that the time-dependent regulation of two key bivalent epigenetic marks, histone H3 trimethylation at lysine 4 (H3K4me3) and histone H3 trimethylation at lysine 27 (H3K27me3), could contribute to the maintenance of the stem cell state and differentiation potential (Harikumar and Meshorer, 2015;Li et al, 2018;Thanuthanakhun et al, 2021). This regulation can take place through epigenetic changes and may be manifested as a "memorizer."…”
Section: Identifying Criteria and Indicators For Assessing External Forcing And Internal Variability-generated Uncertainly In Stem Cell Bsupporting
confidence: 60%
“…In addition, the actin-myosin cytoskeleton is a major "integrator" and "organizer" of mechanical and biochemical signaling inputs that continuously senses, organizes, and integrates these signals using its control "effector" protein belonging to the Rho family of GTPases (Arnold et al, 2017;Kimura et al, 1996). Specially, the antagonistic activities of RhoA and Rac1 GTPases play a role in the dynamics of myosin-mediated contraction and relaxation during cell migration in several cellular settings (Thanuthanakhun et al, 2021). This confirms that the cells adapt to culture environment through the alteration of the Rho-Rho kinase-phospho-myosin pathway, influencing the epigenetic modifications and the transcription factors that contribute to their inherent states (Thanuthanakhun et al, 2021).…”
Section: Identifying Criteria and Indicators For Assessing External Forcing And Internal Variability-generated Uncertainly In Stem Cell Bmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 4, we developed a conceptual framework based on the criteria and indicators of intrinsic disorder within a bioprocess. When abnormal physical force is exerted on cells, cytoskeletal rearrangements are expected to counterbalance the extracellular mechanical forces, trigger signaling cascades, and eventually cause epigenetic modifications (Matthews et al, 2006;Rosowski et al, 2015;Thanuthanakhun et al, 2021). The exact role of this phenomenon and whether it induces the epigenetic modification is still under investigation, but accumulating evidence suggests that mechanical force-driven epigenetic memory formation are important for PSC bioprocess.…”
Section: Identifying Criteria and Indicators For Assessing External Force-and Internal Variability-generated Uncertainty In Stem Cell Biomentioning
confidence: 99%